Sistem Kontrol Motor Pompa Pengisi Tower Air (Tandon) - Ranu Setyobudi; Zainal Abidin; Tijaniyah Tijaniyah (Universitas Nurul Jadid, 2020)
The need for clean water has become a basic need that must be met every day. The community needs a lot of water consumption but sometimes a little. Due to the irregular use of water, it will result in the supply of water in the reservoir will quickly decrease which results in the volume of water in the tendon will run out. Usually to monitor the water supply in the water storage tank (tower) using an ordinary pump, where humans fill the pump continuously or permanently. This has an impact on the reduction of water supply due to erratic usage. The author with the title